Humane Euthanasia in Farm-Raised Foxes - Korhonen, Hannu T (SOSIOHUMANIKA, 2014)
ABSTRACT: The Council Regulation on the protection of animals during killing, No.1099/2009, came to apply from 1st January 2013 onwards. This regulation lays down rules for the killing of animals bred for the production of food, wool, fur, or other products as well as the killing of animals for the purpose of depopulation and for related operations. The Council Regulation also emphasizes the meaning of education, competence, and self-monitoring as means to improve the welfare of animals during killing. It encourages the making of guides to good practice in order to help business operator to plan and monitor the killing process accordingly. The Code of Good Practice (CGP) in humane killing of foxes is created for that purpose. The present CGP aims at providing the highest standards of welfare for farmed foxes (Blue fox Vulpes lagopus, Silver fox Vulpes vulpes, and their colour variants and crossings) in killing. The regulation states many acceptable killing methods for foxes. The key aspects and parameters affecting the humanity of killing of those methods are presented in CGP. However, more practical and detailed description of killing is given for the most used killing method â electrocution. As well as describes the key parameters, the CGP also gives examples of how and why these parameters are to be monitored. According to Council Regulation, all business operators are obligated to plan the killing procedures ahead by drawing up a Standard Operating Procedure (SOP). The CGP gives practical instructions for planning the content of SOP and examples of how the carrying out of SOP should be reported. KEY WORD: Council Regulation, protection of animals, guides to good practice, humane killing of foxes, standard operating procedure, and monitoring.Â RESUME: âPembunuhan Perlahan Manusiawi pada Rubah yang Diternakâ. Peraturan Dewan tentang perlindungan hewan selama pembunuhan, No.1099 / 2009, mulai berlaku dari 1 Januari 2013 ke depan. Peraturan ini menetapkan aturan pembunuhan hewan yang diternak untuk produksi makanan, wol, bulu, atau produk lainnya serta pembunuhan hewan untuk tujuan pengurangan jumlah dan operasi hewan berkenaan. Peraturan Dewan juga menekankan arti pentingnya pendidikan, kompetensi, dan pengawasan-diri sebagai sarana untuk meningkatkan kebaikan bagi hewan saat dibunuh. Hal ini mendorong pembuatan Petunjuk Praktek yang Baik (PPyB) dalam rangka membantu pelaksana lapangan dalam merancang dan memantau proses pembunuhan yang sesuai. PPyB dalam pembunuhan perlahan manusiawi pada rubah dibuat untuk tujuan tersebut. Keberadaan petunjuk itu bertujuan untuk memberikan standar yang tinggi bagi kebaikan rubah yang diternak (rubah berkulit biru âvulpes lagopusâ, rubah berkulit perak âvulpes foxâ, serta rubah dengan kulit belang dan warna-warni) saat dibunuh. Peraturan tersebut menyatakan bahwa banyak metode pembunuhan yang layak bagi rubah. Aspek dan parameter utama yang mempengaruhi metode pembunuhan manusiawi tersaji dalam PPyB tersebut. Namun, penjelasan yang lebih praktis dan rinci tentang pembunuhan diberikan untuk metode pembunuhan yang paling sering digunakan, yaitu disetrum listrik. Selain menjelaskan parameter utama, PPyB juga memberikan contoh tentang bagaimana dan mengapa parameter ini harus diawasi. Menurut Peraturan Dewan, semua pelaksana lapangan diwajibkan untuk merancang prosedur pembunuhan ke depan dengan menyusun Prosedur Pelaksanaan Baku (SOP). PPyB memberikan instruksi praktis untuk merencanakan isi prosedur dan contoh bagaimana pelaksanaan prosedur tersebut harus dilaporkan.KATA KUNCI: Peraturan Dewan, perlindungan hewan, petunjuk praktek yang baik, pembunuhan manusiawi rubah, prosedur pelaksanaan baku, dan pengawasan.About the Author: Prof. Dr. Hannu T. Korhonen is a Researcher at the MTT Agrifood Research Finland, Animal Production Research, SilmÃ¤jÃ¤rventie 2, FI-69100 Kannus, Finland. For academic purposes, heÂ  can be contacted via e-mail at: hannu.t.korhonen@mtt.fiÂ How to cite this article? Korhonen, Hannu T. (2014). âHumane Euthanasia in Farm-Raised Foxesâ in SOSIOHUMANIKA: Jurnal Pendidikan Sains Sosial dan Kemanusiaan, Vol.7(2) November, pp.189-196. Bandung, Indonesia: Minda Masagi Press, UNHAS Makassar, and UNIPA Surabaya, ISSN 1979-0112. Chronicle of the article: Accepted (January 15, 2014); Revised (July 3, 2014); and Published (November 20, 2014).